Manipulasi Identitas Periwayat Hadis Periode Awal: Konsep, Dinamika, dan Kritik - Novizal Wendry (Diroyah : Jurnal Studi Ilmu Hadis, 2022)
This article aims to examine the development of theories, the hadith science, and the manipulative hadith narrators—medallist—which is related to the ethical principle. They massively manipulated the identity of the narrators in the cabin period. It was done by disguising the teacher's identity, suggesting that the teacher was a credible person. The author used qualitative research methods by taking the numbers of sources in the early Islamic period before analyzing them conceptually-relationally. The author found that dynamicity had been done in the attempt to manipulate the narrators, which later the number started to increase as the generation changed. I argued that the manipulations in tadlis are contrary to ethical principles. Internal factors such as the narrator's motivation make the credible hadith effect it. In addition, external factors were also noted, such as the condition of teachers who were still small and were not considered reasonable by hadith critics.